The Solitary Waves in Fluid Filled Elastic Tube with Variable Radius - Nanta Kumar, Umeesh; Choy, Yaan Yee (Enhanced Knowledge in Sciences and Technology, 2021)
the solitary wave modulation in an inviscid fluid filled in an elastic tube with variable radius is studied. The artery is considered as a thin walled and pre-stressed elastic tube with variable radius and the blood is treated as an inviscid fluid. Reductive perturbation method is utilized in the long wave approximation and the various orders of differential equations are obtained. The differential equations are then solved and reduced to nonlinear evolution equation which is the variable coefficient Nonlinear Schrodinger (NLS) equation. After looking a progressive wave type of solution to the nonlinear evolution equation, the graphical outputs are studied and discussed. The results shown that the wave maintained its symmetrical bell-shaped curve propagates to the right as time going. The amplitude of wave remain unchanged when it modulated over the time. This is due to no resistance for blood flowing as the blood in this study is considered as an inviscid fluid.